Conformational Studies of Various Hemoglobins by Natural-Abundance (13)C NMR Spectroscopy - Moon, R. B. (1972)
Studies of variously liganded hemoglobins (both from human and rabbit) by natural-abundance (13)C NMR spectroscopy have revealed apparent conformational differences that have been interpreted on the basis of two quaternary structures for the α(2)β(2) tetramer, and variable tertiary structures for the individual α and β subunits. In solution, rabbit hemoglobins appear to have somewhat more flexibility than human hemoglobins.